A head‐to‐head comparison of personal and professional continuous glucose monitoring systems in people with type 1 diabetes: Hypoglycaemia remains the weak spot. Issue 4 (25th December 2018) - Moser, Othmar; Pandis, Marlene; Aberer, Felix; Kojzar, Harald; Hochfellner, Daniel; Elsayed, Hesham; Motschnig, Melanie; Augustin, Thomas; Kreuzer, Philipp; Pieber, Thomas R.; Sourij, Harald; Mader, Julia K.
Abstract : To compare the performance of a professional continuous glucose monitoring (proCGM) and a personal continuous glucose monitoring (persCGM) system worn in parallel under standardized conditions in individuals with type 1 diabetes (T1D), two CGM systems (iPro2 – proCGM; Minimed 640G – persCGM) worn in parallel using the same sensor (Enlite 2) were compared. Ten people with T1D were included in this single‐centre, open‐label study in which CGM performance was evaluated. The study consisted of a 24‐hours inpatient phase (meals, exercise, glycaemic challenges) and a 4‐day home phase. Analyses included fulfilment of ISO 15197:2013 criteria, mean absolute relative difference (MARD), Parkes Error Grid and Bland–Altman plots. During the inpatient stay, ISO 15197:2013 criteria fulfilment was 58.4% (proCGM) and 57.8% (persCGM). At home, the systems met ISO 15197:2013 criteria by 66.5% (proCGM) and 65.3% (persCGM). No difference of MARD in inpatient phase (19.1 ± 16.7% vs. 19.0 ± 19.6; P = 0.83) and home phase (18.6 ± 26.8% vs. 17.4 ± 21.3%, P = 0.87) was observed. All sensors performed less accurately during hypoglycaemia. ProCGM and persCGM showed similar performance during daytime and night‐time for the inpatient and the home phase. However, sensor performance was reduced during hypoglycaemia for both systems.